2015
DOI: 10.1093/ajh/hpv109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Admission Blood Pressure Indexes for Predicting 30-Day Mortality in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Pulse pressure was an independent predictor of mortality in patients with STEMI, and low admission blood pressure should serve as a warning sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…Older age is an important predictor of worse outcomes in patients with STEMI, including death, bleeding, and ischemic events . As reported in previous studies, admission SBP and HR are predictors of in‐hospital and long‐term mortality . These two important hemodynamic parameters related to cardiovascular functions are closely associated.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Older age is an important predictor of worse outcomes in patients with STEMI, including death, bleeding, and ischemic events . As reported in previous studies, admission SBP and HR are predictors of in‐hospital and long‐term mortality . These two important hemodynamic parameters related to cardiovascular functions are closely associated.…”
Section: Discussionsupporting
confidence: 59%
“…14 As reported in previous studies, admission SBP and HR are predictors of in-hospital and long-term mortality. 15,16 These two important hemodynamic parameters related to cardiovascular functions are closely associated. The double product (DP), which includes both the values of SBP and HR, was initially calculated to indirectly assess myocardial oxygen uptake during stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…A report only recently available from Chinese investigators indicated there was no significant relationship between admission MBP and 30-day mortality in patients with STsegment elevation MI, in which primary PCI was performed in only approximately 12% of the study population. 10) In the present report concerning primary PCI-treated AMI patients, admission MBP < 79 mmHg, an extremely low MBP subset, was tightly associated with higher in-hospital mortality, where- as the other quintiles had almost similar in-hospital mortality rates. We cannot explain the discrepancy in these data; however, it is possible that the presence or absence of patients with cardiogenic shock among the study population might have contributed to these conflicting results.…”
Section: Discussionmentioning
confidence: 47%
“…8,9) However, sufficient data regarding the effects of the steady component of blood pressure, MBP, at admission on the prognosis in AMI patients are still lacking. 10) The AMI-Kyoto Multi-Center Risk Study, a large multicenter observational study in which collaborating hospitals in Kyoto Prefecture have collected demographic, procedural, and outcome data on AMI patients, was established in 2000 in order to analyze this data and establish an emergency-hospital network for heart diseases in Kyoto.…”
Section: B Ased On Numerous Reports From Western Countries Anmentioning
confidence: 99%
“…Limited data exist regarding the potential predictive importance of other bp indices in patients with ACS. In a recent retrospective analysis on 7033 STEMI patients, comparison of admission systolic BP, diastolic BP, pulse pressure, and mean BP showed that only systolic BP and pulse pressure were associated with 30‐day all‐cause mortality …”
Section: Admission Blood Pressure and Patient Outcome In Acute Coronamentioning
confidence: 99%